PENGELOLAAN ZAKAT PROFESI DALAM RANGKA PEMBERDAYAAN MASYARAKAT - Taufiqurrahman, Ahmad (LIPI, 2018)
Abstrak A prominent phenomenon in the world of modern economics is the smaller number of people directly involved with the productive sector and the growing service sector. Because of that salaries, wages, intensive and bonuses are important variables in modern human income whose cumulative values often far exceed the number of commodities listed in the hadith texts, such as agricultural products. The potential of zakat in Indonesia is very large, in 2006 The Frod Foundation estimated that zakat, infaq, and shadaqah funds reached around 19.3 trillion. Unfortunately, this potential has not been utilized optimally so that efforts to empower the community through zakat have not been implemented adequately. What is encouraging at this time is that there have been many zakat management institutions that have sprung up and coupled with public awareness in carrying out zakat also increased. Keyword : Management, Professional Zakat, Community Empowerment